Comparative study of the cytotoxic effect of microcistin-LR and purified extracts from Microcystis aeruginosa on a kidney cell line - Dias, Elsa (2015)
Microcystin-LR (MCLR) is a potent hepatotoxin, but increasing evidences suggest that it might also induce kidney injury. The aim of this work was to evaluate the cytotoxicity of MCLR on a kidney cell line (Vero-E6). Cells were exposed for up to 72 h either to Microcystis aeruginosa extracts from both MCLR-producer and non-MCLR-producer isolates or to pure MCLR (1.5-200 mu M). The cytotoxic effects were evaluated by several cell viability assays (MIT, Neutral Red and LDH). Pure MCLR, the extract from MCLR-producer and the mixture of the non-MCLR-producer with pure MCLR, induced cell viability decrease in a similar dose/time-dependent manner. Conversely, no effects were induced by the extract of non-MCLR-producer. These results suggest that the cytotoxic effects of M. aeruginosa extract were due to MCLR and excluded the eventual toxicity of other cyanobacteria bioactive compounds. The lowest cytotoxic MCLR concentration varied between 11 and 100 mu M depending on the employed cell viability assay and is within the range of MCLR dosage reported to affect other mammalian cell lines. The NR assay was the most sensitive to evaluate the MCLR-induced cytotoxicity. Our results suggest that Vero-E6 cell line may constitute a cell model to evaluate the nephrotoxicity of microcystins. (C) 2009 Elsevier Ltd. All rights reserved.. - Portuguese Foundation for Science and Technology [SFRH/BD/10585/2002]; National Health Institute, Portugal. - To Portuguese Foundation for Science and Technology for grants SFRH/BD/10585/2002 attributed to Elsa Dias. To National Health Institute, Portugal, for a master fellowship attributed to Mariana Andrade. To Institute for Medicines and Pharmaceutical Sciences (I-Med) and to Centre for Research on Human Molecular Genetics (CIGMH).